2021
DOI: 10.2174/1381612827666210804110139
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Connections between Schizophrenia, Antipsychotic Drugs and Metabolic Syndrome: A Variety of Players

Abstract: Background: Diagnosis of schizophrenia lacks of reliable medical diagnostic tests and robust biomarkers applied to clinical practice. Schizophrenic patients undergoing treatment with antipsychotics suffer a reduced life expectancy due to metabolic disarrangements that co-exist with their mental illness and predispose them to develop metabolic syndrome, also exacerbated by medication. Metabolomics is an emerging and potent technology able to accelerate this biomedical research. Aim: This review focus on a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 119 publications
2
8
0
Order By: Relevance
“…Prior studies have also found acylcarnitines levels with abnormalities in the plasma of patients with schizophrenia and familial Mediterranean fever (Kiykim et al, 2016;Cao et al, 2020). Moreover, the regulation of L-carnitine metabolites by antipsychotic drugs has been reported in clinical studies (Lheureux and Hantson, 2009;Molina et al, 2021;Yi et al, 2021), and in animal studies (Albaugh et al, 2012;, particularly in two early studies in patients with schizophrenia after treatment (Kriisa et al, 2017;Cao et al, 2019b). All these findings support our finding that the carnitine pathway can be regulated by OLA.…”
Section: Discussionsupporting
confidence: 90%
“…Prior studies have also found acylcarnitines levels with abnormalities in the plasma of patients with schizophrenia and familial Mediterranean fever (Kiykim et al, 2016;Cao et al, 2020). Moreover, the regulation of L-carnitine metabolites by antipsychotic drugs has been reported in clinical studies (Lheureux and Hantson, 2009;Molina et al, 2021;Yi et al, 2021), and in animal studies (Albaugh et al, 2012;, particularly in two early studies in patients with schizophrenia after treatment (Kriisa et al, 2017;Cao et al, 2019b). All these findings support our finding that the carnitine pathway can be regulated by OLA.…”
Section: Discussionsupporting
confidence: 90%
“…Because Trp and fatty acids metabolism is greatly affected by individuals, such as gender, age, eating habits, and smoking [ 7 , 68 ], the recruited cases are relatively small and the results still need a large sample to explore further. Meanwhile, considering that antidepressant and antipsychotic drugs could affect Trp and fatty acids metabolism [ 69 , 70 , 71 ], the influence of drugs on plasma Trp metabolites and the composition of fatty acids cannot be excluded. In addition, the detection methods based on mass spectrometry require expensive equipment and may lead to discrepancies in results.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have also found acylcarnitines levels with abnormalities in the plasma of patients with schizophrenia and familial Mediterranean fever ( Kiykim et al, 2016 ; Cao et al, 2020 ). Moreover, the regulation of L-carnitine metabolites by antipsychotic drugs has been reported in clinical studies ( Lheureux and Hantson, 2009 ; Molina et al, 2021 ; Yi et al, 2021 ), and in animal studies ( Albaugh et al, 2012 ; Jiang et al, 2019 ), particularly in two early studies in patients with schizophrenia after treatment ( Kriisa et al, 2017 ; Cao et al, 2019b ). All these findings support our finding that the carnitine pathway can be regulated by OLA.…”
Section: Discussionmentioning
confidence: 99%